La controverse Doyère-Pouchet sur la reviviscence animale et ses échos dans L’Homme à l’oreille cassée d’Edmond About - Sukiennicka, Marta (Studia Romanica Posnaniensia, 2020)
Rotifers and tardigrades, microscopic animals discovered in the 18th century, have exceptional abilities to survive in hostile conditions. Exposing them to desiccation, extreme temperatures, and vacuum, scientists wanted to determine whether these animals die and revive, or whether they preserve a trace of life in these lethal conditions. The question of boundaries of life had been the subject of scientific controversy throughout the 19th century, an example of which was the debate between L. Doyère and F.-A. Pouchet in the late 1850s. Its echoes can be found in E. About’s science-fiction novel L’Homme à l’oreille cassée (1861), in which tardigrades’ ability to revive is extrapolated to humans.